Corporate Climate Change- Related Accounting and Taxation: A Comparative Analysis of Portuguese and Spanish Frameworks on GHG Emissions Allowances - Monteiro, Sónia (2023)
This chapter aims to provide an overview of corporate climate change-related accounting and taxation practices in Portugal and Spain. The Portuguese Accounting and Financial Reporting Standard No. 26: Environmental Matters and the Spanish Royal Decree 602/2016 establish the current accounting treatment for greenhouse (GHG) emissions. While the initial measurement basis is the same in both countries (cost when licenses are acquired or fair value when obtained for free), the accounting regulations prescribe different accounting treatments for the initial recognition. In Spain, allowances are recognized as inventories, while in Portugal, they are recognized as intangible assets. Interestingly, the Portuguese regulation uses the FIFO inventory method to calculate the amortization of the intangible asset. Regarding corporate income tax, there is no specific treatment for emission allowances in either country’s tax legislation. Additionally, a reverse-charge mechanism on CO2 emissions trading has been introduced in Europe, resulting in no differences between countries concerning VAT.